2019
DOI: 10.51983/arss-2019.8.2.1588
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility of Selected Businesses in Cebu City, Philippines

Abstract: Corporate social responsibility (CSR) involves enhancing the personal satisfaction of the workforce and their families just as of the nearby network and society everywhere with the proceeding with responsibility by business to act morally and add to financial enhancement. This study determined the benefits of businesses from engaging in CSR programs. This study applied the descriptive method. This study utilized the researcher-made questionnaire to gather data on the characteristics of the business, the profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In that case, such customers can convince other customers to support the business because, through the consummation of goods or services, those customers already support charities or the environment (The Elusive Green Consumer, 2022). Bueno et al (2019) have noticed a growth in the number of entities and corporate organizations engaging in Corporate Social Responsibility (CSR) for a myriad of benefits, wherein the most crucial factor is the ability to support the community where they operate and be open to societal demands thereby, CSR has demonstrated that some businesses addressed these considerations by allocating additional resources to CSR (Agan et al, 2016;Brammer & Millington, 2005;Lantos, 2001). However, management at some firms has objected, saying that further CSR spending is incompatible with efforts to increase profitability (Reverte et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In that case, such customers can convince other customers to support the business because, through the consummation of goods or services, those customers already support charities or the environment (The Elusive Green Consumer, 2022). Bueno et al (2019) have noticed a growth in the number of entities and corporate organizations engaging in Corporate Social Responsibility (CSR) for a myriad of benefits, wherein the most crucial factor is the ability to support the community where they operate and be open to societal demands thereby, CSR has demonstrated that some businesses addressed these considerations by allocating additional resources to CSR (Agan et al, 2016;Brammer & Millington, 2005;Lantos, 2001). However, management at some firms has objected, saying that further CSR spending is incompatible with efforts to increase profitability (Reverte et al, 2016).…”
Section: Introductionmentioning
confidence: 99%